Revolutionizing aqueous batteries: Exploring the challenges and thriving advancements - Mishra R.; Malviya M.; Tiwari P. (My University, 2025)
Aqueous batteries have garnered considerable attention due to their cost-effectiveness, safety features, high ionic conductivity, and eco-friendliness. However, they also face several critical challenges that hinder their widespread adoption. These include a narrow electrochemical stability window of water (∼1.23 V), which restricts the operating voltage of the battery and limits energy density. In addition, dendrite growth on metal anodes (particularly zinc) can lead to short-circuiting and capacity fading. Other issues involve poor cycling stability, gas evolution (hydrogen/oxygen) due to water decomposition, low Coulombic efficiency, and the corrosive nature of aqueous electrolytes, which degrade electrode materials over time. This study delves into the obstacles and recent resolutions for aqueous battery systems utilizing carrier ions such as sodium, magnesium, zinc, aluminium, and lithium. Its primary objective is to demonstrate the potential of aqueous batteries as a feasible and sustainable option in the evolving energy storage technologies. Progress in materials science and innovative design approaches are essential in surmounting these challenges. By scrutinizing key advancements in electrode materials, electrolyte compositions, and battery structures, this study spotlights the continuous endeavors to refine and commercialize aqueous batteries. Additionally, this study evaluates research papers published from 2014 to the current period, offering a comprehensive summary of advancements in the field. © 2025 Elsevier Ltd